2014
DOI: 10.1007/s10616-013-9681-0
|View full text |Cite
|
Sign up to set email alerts
|

A review of the genotoxic and carcinogenic effects of aspartame: does it safe or not?

Abstract: The objective of this article is to review genotoxicologic and carcinogenic profile of the artificial sweetener aspartame. Aspartame is a synthetic dipeptide, nearly 180-200 times sweeter than sucrose. It is the most widely used artificial sweetener especially in carbonated and powdered soft drinks, beverages, drugs and hygiene products. There is a discussion ongoing for many years whether aspartame posses genotoxic and carcinogenic risk for humans. This question led to many studies to specify the adverse effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 30 publications
1
16
1
3
Order By: Relevance
“…On the contrary, the present results disagreed with who recorded that ASP had a moderate genotoxic effect [77]. Also, ASP and acesulfame-K administration induced no significant increase in the frequency of CA in Swiss albino mice bone marrow cells [78].…”
Section: The Effect On the Chromosomal Aberration Frequencycontrasting
confidence: 99%
“…On the contrary, the present results disagreed with who recorded that ASP had a moderate genotoxic effect [77]. Also, ASP and acesulfame-K administration induced no significant increase in the frequency of CA in Swiss albino mice bone marrow cells [78].…”
Section: The Effect On the Chromosomal Aberration Frequencycontrasting
confidence: 99%
“…Conversely, previous studies have also reported that it did not increase sister chromatid exchange (SCE) [28,29] and was not mutagenic at Ames test analysis involving Salmonella typhimurium strains [29,30]. Otherwise, APM was described as a moderately genotoxic agent [31]. However, it was reported that no evidence of gene mutation induction in a series of bacterial mutation tests, and that although there was evidence of in vitro chromosome damage induction, this occurred secondary to cytotoxicity and did not involve primary DNA damage [32].…”
Section: Discussionmentioning
confidence: 90%
“…patients (2) . It is found in many products, including soft drinks, chewing gum, candy, yogurt, and some pharmaceutical products, such as vitamins and sugar free cough drops (3) According to recommendations from FDA and the JECFA (Joint FAO/WHO Expert Committee on Food Additives), the acceptable daily intake of aspartame is 50 mg/ kg and 40 mg/kg per day, respectively (4,5) . Although, the Food and Drugs Administration and other advisory agencies have considered ASP to be safe in acceptable daily intake range, however some experimental and epidemiological studies have recently reported that ASP consumption at abuse doses results in some adverse effects such as obesity (6,7) , nephrotoxicity (8) , metabolic syndrome (9) , cancer (10,11) , and adverse neurobehavioral effects (12) .…”
Section: Introductionmentioning
confidence: 99%